2022
DOI: 10.1093/noajnl/vdac102
|View full text |Cite
|
Sign up to set email alerts
|

Butterfly glioblastoma: Clinical characteristics, treatment strategies and outcomes in a population-based cohort

Abstract: Background Butterfly glioblastoma is a rare subgroup of glioblastoma with a bihemispheric tumor crossing the corpus callosum, and is associated with a dismal prognosis. Prognostic factors are previously sparsely described and optimal treatment remain uncertain. We aimed to analyse clinical characteristics, treatment strategies and outcome from butterfly glioblastoma in a real-world setting. Methods This retrospective populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Despite technological advances, established and described techniques for resection of these tumors, and evidence favorable to this strategy, surgery is still little used in the primary treatment of BG [4,9,11]. This is possibly due to the poor results reported in the past and the lack of know-how and expertise of neurosurgeons in this type of intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite technological advances, established and described techniques for resection of these tumors, and evidence favorable to this strategy, surgery is still little used in the primary treatment of BG [4,9,11]. This is possibly due to the poor results reported in the past and the lack of know-how and expertise of neurosurgeons in this type of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Gliomas are one of the most common primary neoplasm of the central nervous system (CNS) (25,5% of cases) and the most common malignant brain tumor in the adult population (80,8% of cases) [1]. A growth pattern involving both radial hemispheres and the corpus callosum, termed butter y glioma (bG), is usually associated with poor prognosis, short survival, di cult management, cognitive impairment, and functional rapid movement [2][3][4][5]. Despite the histology most commonly seen to be glioblastoma (GB), this growth pattern can also be seen in low-grade gliomas and in lymphoproliferative disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subset of bGBM has been proven to have worse outcomes as compared with other GBMs but can be improved with cytoreduction. 1,[20][21][22] A review of National Cancer Database by Baoro et al showed that surgical resection improved the OS to 11.5 months as compared with 6.5 months with a biopsy alone. 21 However, a meta-analysis by Chawla et al 22 noted a significantly high rate of complications with surgery as opposed to biopsy (28% vs 13%; P < .01).…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma (GBM) is the most common and malignant form of glioma, with a median survival below 18 months and a five-year survival rate of less than 10% 1 . A major challenge in the treatment of GBM is that by the time of diagnosis, highly infiltrative tumor cells have already migrated across long distances on major white matter tracts and/or the microvasculature to invade surrounding brain regions 2 . Thus, despite the use of fluorescence guided surgery for maximal resection of tumor tissues followed by concurrent chemotherapy with temozolomide (TMZ) and conformal radiation [3][4][5] , recurrence is unavoidable since elimination of all residual cells is not possible.…”
Section: Introductionmentioning
confidence: 99%